Clinical characteristics of infants hospitalized with early congenital syphilitic nephropathy: a single-center retrospective cross-sectional study in China - Caiying Wang; Wenhui Lun; Lin Pang (BMC, 2023)
Abstract Background Early studies claimed that early congenital syphilitic (CS) nephropathy was rare, and systematic studies about this disease are absent, which may lead to poor awareness of early CS nephropathy in clinicians and result in misdiagnosis and poor patient prognosis. The present study systematically and comprehensively analyzes the clinical characteristics of infants with early CS nephropathy hospitalized in Beijing Ditan Hospital, an infectious disease hospital in China in order to improve the understanding and management of this disorder. Methods Data of the children with early CS from July 1, 2008, to December 31, 2021, were collected from the electronic medical record system of the hospital. Each patient's demographic characteristics, clinical history, mother's history of syphilitic infection, and laboratory values were extracted. The patients were enrolled to either the nephropathy group or the non-nephropathy group depending on diagnosis. Descriptive statistics was used to report basic demographics, clinical and laboratory test values, and variables were compared between the two groups by nonparametric tests, t test or χ 2 tests. Results Of the 122 children with early CS enrolled, 24(19.7%) were diagnosed with early CS nephropathy. All of the children with CS nephropathy were young infants < 6 months old. A majority of them showed typical congenital syphilitic skin lesions, but a quarter of them did not have skin lesions. Compared with non-nephropathic children with early CS, those with nephropathy had higher frequency of hepatosplenomegaly, fever, edema, gastrointestinal (GI) symptoms, and anemia, as well as decreased C3 levels. Urinalysis results showed hematuria in all patients with early CS nephropathy, with proteinuria and renal function impairment in 91.7% and 12.5% of the patients, respectively. Nephritic-type nephrotic syndrome and glomerulonephritis were diagnosed in 45.8% and 54.2% of these patients, respectively. All infants with CS nephropathy were cured or improved after appropriate treatments. Conclusion Infants with early CS nephropathy often presented with nephritic-type nephrotic syndrome or glomerulonephritis, and the typical skin lesions, fever, hepatosplenomegaly, and edema, etc., were its common clinical presentations, and these characteristics could help with the diagnosis. But for infants with nephropathy who did not have typical clinical presentations, CS should also be screened as an important etiology to avoid misdiagnosis.